After Prison: Navigating Employment and Reintegration - Ricciardelli, Rose; Peters, Adrienne M.F. (Wilfrid Laurier University Press, 2017)
[This book] opens with a former prisoner's story of reintegration employment experiences. Next, relying on a combination of research interviews, quantitative data, and literature, contributors present an international comparative review of Canada's evolving criminal record legislation; the promotive features of employment; the complex constraints and stigma former prisoners encounter as they seek employment; and the individual and societal benefits of assisting former prisoners attain "gainful" employment. A main theme throughout is the interrelationship between employment and other central conditions necessary for safety and sustenance. [The] book offers suggestions for criminal record policy amendments and new reintegration practices that would assist individuals in the search for employment. Using the evidence and research findings of practitioners and scholars in social work, criminology and law, psychology, and other related fields, the contributors concentrate on strategies that will reduce the stigma of having been in prison; foster supportive relationships between social and legal agencies and prisons and parole systems; and encourage individually tailored resources and training following release of individuals. --Publisher's description. Contents: Section I – The Employment–Re-entry Enigma/Dilemma. Work after prison: one man's transition / James Young [pseudonym] -- Employment and desistance from crime / Kemi S. Anazodo, Christopher Chan, and Rose Ricciardelli -- Employment and criminal offenders with mental illness / Krystle Martin. Section II – Criminal Histories, Employment Prospects, and Moving Forward. Job search, suspended: changes to Canada's Pardon Program and the impact of finding employment / Samantha McAleese -- Vulnerabilities and barriers in post-release employment reintegration as indicated by parolees / Rose Ricciadelli and Taylor Mooney. Section III - Employment reintegration programming: supportive strategies and related outcomes. Is criminal history at the time of employment predictive of job performance? : A comparison of disciplinary actions and terminations in a sample of production workers / Mark G. Harmon, Laura J. Hickman, Alexandra M. Arneson, and Ashley M. Hansen -- Transforming rehabilitation: a critical evaluation of barriers encountered by an offender rehabilitation program for South Asian/Muslim offenders within the new probation service model / Christine Victoria Hough -- Promoting employment opportunities through mentorship for gang-involved youth reintegrating into the community / Adrienne M.F. Peters -- Barriers to community reintegration: the benefits of client-centred case management and pre-employment skills training / Ashley Brown. Section IV - The employment reintegration of unique populations. "Between a rock and a hard place": how being a "convict" hinders finding work in the neo-liberal, late-capitalist economy / Dale C. Spencer -- Does the "wrongful" part of wrongful conviction make a difference in the job market? / Kimberley A. Clow -- Conclusion. Employment reintegration / Rose Ricciardelli and Adrienne M.F. Peters.
Keywords: Canada. BUSINESS & ECONOMICS; Canada. Criminals; Employment; Employment. Genre/Form: Electronic books; Ex-convicts; Labor & Industrial Relations. Criminals; Labor. POLITICAL SCIENCE; Rehabilitation; Rehabilitation. Ex-convicts